Pengaruh Price Earning Ratio (PER), Current Ratio (CR), Total Asset Turnover (TAT), Net Profit Margin (NPM), dan Debt To Equity Ratio (DER) Terhadap Return Saham Syariah yang Terdaftar di Bursa Efek Indonesia: Perusahaan Sub Sektor Makanan dan Minuman Periode Januari - Desember Tahun 2023 - Nessa Amanah; Idwal B; Herlina Yustati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the influence of the Price Earning Ratio (PER), Current Ratio (CR), Total Assets Turnover (TAT), Net Profit Margin (NPM), and Debt To Equity Ratio (DER) partially on Sharia Stock Returns Food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period January-December 2023. This type of research is quantitative research in the form of comparative and time series. The method used in the data collection technique in this research is a purposive sampling data collection technique and the data used in this research is quantitative data. The data collection techniques used are library research and documentation. From the research results it can be concluded as follows: 1. The PER variable has a positive and significant effect on Sharia Stock Returns. 2. The CR variable has a not positive and significant effect on Sharia Stock Returns. 3. The TAT variable has a positive and significant effect on Sharia Stock Returns. 4. The NPM variable has a positive and significant effect. significant on Sharia Stock Returns 5. The DER variable has a not positive and significant effect on Sharia Stock Returns